ĐÁNH GIÁ RỦI RO TRONG TÌM KIẾM THĂM DÒ DẦU KHÍ TẠI BỂ SÔNG HỒNG - Hậu, Đỗ Văn; Vũ, Phạm Năng; Giang, Lê Thị Lam (Vietnam Journal of Earth Sciences, 2017)
Since 1960 of the last Century upto now a lot of geological - geophysical data was collected by theoil exploration in Vietnam. In the area of the Red River Basin more than 100 structures expected for oil and gas potential were observed. Hence the Basin is complicated in geological structure, that can be the reason of high level of risk in determination of drilling location.During fue time period 1981 - 1989 some foreign exploration companies carried out the geological risk assessement before drilling decision. However the drilling results indicated a big difference in comparison with the estimation.By making the correlation between the mentioned above drilling results and geological -geophysical data, the procedure for risk assessement is more improved. In fact the reestimation of the probability carried out by the authors of this paper indicated a good consistency between the drilling results with oil and gas potential iri the area. This technique was appliedfor the risk assessement before drilling in numerous locations of the Red River Basin for the last 4 years. The results showed a good agreement between the drilling data and oil with gas potential. ·